Design, synthesis, and biological evaluation of novel 6-(pyridin-3-yl) quinazolin-4(3H)-one derivatives as potential anticancer agents via PI3K inhibition. (15th September 2021) - Yang, Huarong; Li, Qing; Su, Mingzhi; Luo, Fang; Liu, Yahua; Wang, Daoping; Fan, Yanhua
Graphical abstract: Abstract: Abnormal activation of the PI3K/Akt pathway is demonstrated in most of human malignant tumors via regulation of proliferation, cell cycle, and apoptosis. Therefore, drug discovery and development of targeting the PI3K/Akt pathway has attracted great interest of researchers in the development of anticancer drugs. In this study, fifteen 6-(pyridin-3-yl) quinazolin-4(3 H )-one derivatives were designed and synthesized. Anticancer activities of the synthetic compounds were evaluated and the potential mechanisms were explored. Several compounds showed certain proliferation inhibitory activity against the tested cancer cells including human non-small cell lung cancer (NSCLC) HCC827, human neuroblastoma SH-SY5Y and hepatocellular carcinoma LM3 cells. Among them, compound 7i and 7m showed the best inhibitory activity against all the cancer cell lines and more active against HCC827 cells with IC50 values of 1.12 μM and 1.20 μM, respectively. In addition, 7i and 7m showed lower inhibitory activity against H7702 cells (human normal liver cells) with IC50 values of 8.66 μM and 10.89 μM, respectively, nearly 8-fold lower than that in HCC827 cells. These results suggested that compounds 7i and 7m had certain selectivity to tumor cells, compared to human normal cells. Further biological studies indicated 7i induced G2/M phase arrests and cell apoptosis of HCC827 cells via PI3K/Akt and caspase dependent pathway. Together, these novel 6-(pyridin-3-yl) quinazolin-4(3 H )-one derivatives such as compound 7i and 7m might be lead compounds for development of potential anti-cancer drugs.